2003
DOI: 10.1021/ja037368r
|View full text |Cite
|
Sign up to set email alerts
|

Schulzeines A−C, New α-Glucosidase Inhibitors from the Marine Sponge Penares schulzei1

Abstract: Three new alpha-glucosidase inhibitors, schulzeines A-C (1-3), were isolated from the marine sponge Penares schulzei. Their structures were elucidated by spectral analysis and chemical degradations to be the isoquinoline alkaloids, encompassing two amino acids, and C(28) fatty acid, the last of which was sulfated. Absolute stereochemistry of schulzeines was determined by application of the modified Mosher analysis to fragments obtained by chemical degradation. Schulzeines A-C inhibit alpha-glucosidase with IC(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 18 publications
3
70
0
1
Order By: Relevance
“…Three new isoquinoline alkaloids, schulzeines A (8), B (9), and C (10), were isolated from the marine sponge Penares schulzei [17]. Schulzeines A-C encompass two amino acids and a C 28 fatty acid, the last of which was sulfated.…”
Section: Alkaloids Tinospora Cordifoliamentioning
confidence: 99%
See 2 more Smart Citations
“…Three new isoquinoline alkaloids, schulzeines A (8), B (9), and C (10), were isolated from the marine sponge Penares schulzei [17]. Schulzeines A-C encompass two amino acids and a C 28 fatty acid, the last of which was sulfated.…”
Section: Alkaloids Tinospora Cordifoliamentioning
confidence: 99%
“…Schulzeines A-C encompass two amino acids and a C 28 fatty acid, the last of which was sulfated. Schulzeines A-C inhibit α-glucosidase with IC 50 values of 48-170 nM [17].…”
Section: Alkaloids Tinospora Cordifoliamentioning
confidence: 99%
See 1 more Smart Citation
“…and schulzeines A-C (Penares schulzei), which inhibits a-glucosidase with IC 50 values between 48 and 170 nM. 12 However, no chemistry has been reported from sponges belonging to the genus Ecionemia.…”
Section: Introductionmentioning
confidence: 99%
“…7,8) Furthermore, recent investigations have reported that the compounds with cinnamic amide unit have strong a-glucosidase inhibition activities. [9][10][11] These motivated us to carry out further structural modifications on oleanolic acid by incorporating different cinnamic amide units.In the present paper, a series of analogues with the oleanolic acid core and different cinnamic amide ligands were designed, synthesized, and evaluated as a-glucosidase inhibitors (Fig. 1, Table 1).…”
mentioning
confidence: 99%